866. Adherence to F/TDF for PrEP in Dried Blood Spots and HIV Infection Rates: A Pooled Analysis of Global PrEP Studies. (4th December 2021) - Liu, Albert; Liu, Albert; Grant, Robert; Landovitz, Raphael J; Landovitz, Raphael J; Grinsztejn, Beatriz; Celum, Connie; Baeten, Jared; Magnuson, David; Das, Moupali; Carter, Christoph C; Smith, Dawn; et al.
Abstract: Background: The use of daily F/TDF for HIV pre-exposure prophylaxis (PrEP) substantially reduces HIV acquisition. Dried blood spot (DBS) tenofovir-diphosphate (TFV-DP) levels reflect TDF use over the past 6-8 weeks, providing an objective measure of adherence in people taking PrEP. Methods: In a pooled analysis of 19 PrEP demonstration projects and clinical studies, 6, 613 participants had at least one TFV-DP measurement in DBS and followed for at least 48 weeks and up to 96 weeks. We used a piecewise linear mixed-effects model to plot the least-square means with corresponding 95% confidence intervals (CI) of TFV-DP for adherence over time, and Poisson regressions to calculate HIV incidence rates (IR) by level of weighted average of TFV-DP. Results: Of 6, 613 participants, median age was 30 years (interquartile range 24−38), 5, 449 (82%) were cisgender men, 806 (12%) were cisgender women, and 349 (5%) were transgender (316 transgender women, 2 transgender men, 31 unspecified). Adherence based on TFV-DP in DBS was consistently higher among participants who did not acquire HIV compared to those who did (Figure). Among all participants, 21%, 14%, 36%, and 29% has DBS consistent with taking < 2, 2−3, 4−6, and ≥7 tablets of F/TDF PrEP per week (Table). Sixty-nine participants acquired HIV, with a median PrEP exposure of 0.82 years and an overall HIV IR (95% CI) of 1.16 (0.92, 1.47) per 100 person years. There was a strong association between adherence and HIV incidence [among individuals who took < 2, 2−3, 4−6, and ≥7 tablets/week, the HIV IRs (95% CI) were 5.20 (4.03, 6.71), 0.38 (0.12, 1.18), 0.28 (0.12, 0.61), and 0.06 (0.01, 0.39), respectively. Overall IR (95% CI) of HIV infection among cisgender men was 1.25 (0.98, 1.60) per 100 patient-years. Four cisgender women and 2 transgender participants acquired HIV, corresponding to IRs (95% CI) of 0.71 (0.27, 1.90) and 0.63 (0.16, 2.53). Adherence by TFV-DP in DBS for F/TDF users who acquired HIV compared to those who did not. Note: 'x' on the Figure represents visit week when a new HIV infection was detected. HIV incidence rates (95% confidence intervals) by adherence to PrEP measured by level of TFV-DP in DBS up to 96 weeks after PrEP Initiation Conclusion: This diverse, multi-national pooled analysis of F/TDF PrEP use provides the largest assessment to date of the adherence-HIV incidence relationship in people taking F/TDF for PrEP. The results suggest a high background HIV incidence in the pooled cohort and high efficacy in those adherent to PrEP. These findings support ongoing efforts to increase PrEP use among people who would benefit. Disclosures: Albert Liu, MD, MPH, Gilead Sciences (Individual(s) Involved: Self): Gilead has donated study drug for studies I have led., Grant/Research Support, Other Financial or Material Support, Research Grant or Support; IAS-USA (Individual(s) Involved: Self): Honorarium for manuscript writing, Other Financial or Material Support; Viiv Healthcare (Individual(s) Involved: Self): Grant/Research Support, Research Grant or Support Raphael J. Landovitz, MD, MSc, Gilead Sciences (Individual(s) Involved: Self): Consultant; Janssen (Individual(s) Involved: Self): Consultant; Merck Inc (Individual(s) Involved: Self): Consultant; Roche (Individual(s) Involved: Self): Consultant Jared Baeten, MD, PHD, Gilead Sciences Inc. (Employee, Shareholder) David Magnuson, PharmD, Gilead Sciences Inc (Employee, Shareholder) Moupali Das, MD, Gilead Sciences Inc. (Employee, Shareholder) Christoph C. Carter, MD, Gilead Sciences Inc. (Employee, Shareholder) Li Tao, MD, PhD, Gilead Sciences Inc (Employee, Shareholder)